Technology at work: the future of innovation and employment - Frey, Carl Benedikt; Osborne, Michael (London, 2015)
"Technology at Work: The Future of Innovation and Employment, is the latest Citi GPS report from the Oxford Martin School and Citi. It explores trends in automation and points to sluggish job creation caused partly by increasing automation, and argues that secular stagnation in the digital age can only be avoided by a shift towards inclusive growth. The authors highlight the key challenges, explore some of the new technology brought on by the digital age and set out an agenda for change, calling for long term thinking to mitigate the negative effects of an ever more automated and digital economy."